Language Learning Strategies of a Polyglot: Bridging Theory and Practice (ELS Journal on Interdisciplinary Studies in Humanities, 2025)
Second language acquisition (SLA) research has extensively examined language learning in formal, often monolingual, classroom settings, there is a noticeable lack of empirical investigation into how polyglots acquire, manage, and sustain multiple languages. This gap is particularly significant given the rising importance of multilingualism in a globalized world and the proven cognitive, cultural, and professional benefits it offers. This qualitative case study examines the language learning strategies of Indonesian polyglot proficient in seven languages: Indonesian, English, Mandarin, Korean, Japanese, Arabic, and Latin. Through a purposive sampling method, the participant was interviewed via Zoom, and data were analysed using Oxford’s (1990) taxonomy of language learning strategies. The study identified both direct strategies (memory, cognitive, compensation) and indirect strategies (metacognitive, affective, social) used by the participant. Findings reveal that the participant’s language proficiency is achieved through a strategic integration of diverse methods tailored to specific goals and contexts. Motivation driven by extrinsic factors like scholarships, personal interests, and intrinsic spiritual reasons played an important part of learning a language intensity. The participant preferred structured tools, analytical comparisons, and regular practice, while affective and social strategies helped manage emotional challenges and maintain motivation. This study supports Oxford’s framework and highlights the importance of clear goals, sustained motivation, and community engagement in successful multilingual acquisition.
Keywords: Language Learning Strategies; Multilingual Proficiency; Oxford’s Taxonomy